PERDAGANGAN KAPAS PADA MASA BALI KUNO BERDASARKAN PRASASTI KINTAMANI D DAN E (KAJIAN EPIGRAFI) - Destriana, Novita (Humanis; Volume 7. No. 2. Mei 2014, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Trade is an economic activity than can not be saparated for the survival in the context of welfare. Trade is a reciprocal relationship that perfomed by at least two parties, in an effort to get the goods through the exchange which emphasizes aspect of the needs of the social aspect. This can be seen in the inscripsion Kintamani D and E which are found in the village of Kintamani. Based on this background, related to two problems. This research is intended to solve some problems of factor influence trade of catton in Kintamani and the role of government and the system of the cotton ttrade in Kintamani. This study in aimed at obtaining the solutions through some inscriptions. The data is then analyzed, interpretated and synthesized, and the result subunit as a report. The method used in this study method of data collection in the form of incriptions ready translated and analized. The final stage in this research is the presentation of the thesis stage. The result of this study are as follows : factors affecting the trade on a large scale in the village of Kintamani because Kintamani a supplier of cotton at the time so that abundant stoct of cotton. Government also greatly contribute in implemnting trade regulations delegated to the Nayaka Kapas and use the system trade round shouldered by or through market. The result of this research can be use as a reference for future studies related to trade during anciant Bali and also in preservation related to an axisting site in Kintamani region. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: cotton trade, commodity, inscriptions